Wege aus der Wirtschaftskrise und Möglichkeiten zur Wiederherstellung der Wirtschaftlichen Stabilität in Estland. Võimalused ja suunad majanduskriisist väljumiseks ning edasise stabiilsuse saavutamiseks Eestis - Raudjärv, Matti (Estonian Discussions on Economic Policy, 2010)
The paper gives a concise evaluation of the impacts of the global economic crisis on the Estonian economy in 2009-2010. The main activities performed in the Estonian economy for the alleviation of the crisis have been pointed out. The state budget and its cuts are dwelt upon. Changes in the Estonian economy within the last few years are presented with the related brief assessments. The measures officially planned by government agencies for the current and further stabilisation of the Estonian economy are described. The main activities that should be performed in Estonia in the opinion of the author for the alleviation of and exiting the crisis are pointed out. As overcoming the economic crisis and achievement of subsequent stable development assumes also carrying out several reforms, the paper also briefly dwells on the problems related to the achievement of regional balance and the administrative-territorial reform